Ral mediates activity‐dependent growth of postsynaptic membranes via recruitment of the exocyst. (28th June 2013) - Teodoro, Rita O; Pekkurnaz, Gulçin; Nasser, Abdullah; Higashi‐Kovtun, Misao E; Balakireva, Maria; McLachlan, Ian G; Camonis, Jacques; Schwarz, Thomas L
<x xml:space="preserve">Abstract</x> Remodelling neuronal connections by synaptic activity requires membrane trafficking. We present evidence for a signalling pathway by which synaptic activity and its consequent Ca2+ influx activate the small GTPase Ral and thereby recruit exocyst proteins to postsynaptic zones. In accord with the ability of the exocyst to direct delivery of post‐Golgi vesicles, constitutively active Ral expressed in Drosophila muscle causes the exocyst to be concentrated in the region surrounding synaptic boutons and consequently enlarges the membrane folds of the postsynaptic plasma membrane (the subsynaptic reticulum, SSR). SSR growth requires Ral and the exocyst component Sec5 and Ral‐induced enlargement of these membrane folds does not occur in sec5−/− muscles. Chronic changes in synaptic activity influence the plastic growth of this membrane in a manner consistent with activity‐dependent activation of Ral. Thus, Ral regulation of the exocyst represents a control point for postsynaptic plasticity. This pathway may also function in mammals as expression of activated RalA in hippocampal neurons increases dendritic spine density in an exocyst‐dependent manner and increases Sec5 in spines.